Women’s Empowerment Through Microfinance: A Case Study of Mero Laghubitta Bittiya Sanstha Limited, Bedkot Municipality, Kanchanpur - Bam, Nirmala Kumari (Journal of Durgalaxmi, 2024)
This research study explores the role of microfinance in empowering women and evaluating their participation in microfinance initiatives. Using a mixed-methods approach, it examines women’s engagement through the Mero Microfinance Program (MFP) in Bedkot Municipality-7, Kanchanpur, Nepal. Employing a descriptive and exploratory research design, the study analyzes primary and secondary data from 305 groups under MFP, consisting of 1,400 members, including 170 women-led groups with 545 members. A simple random sampling method was used to select 119 women group leaders with a 5 percent margin of error, 50 percent population proportion, and 95 percent confidence level. Microfinance programs targeting rural and marginalized populations address critical issues such as poverty, illiteracy, unemployment, and limited decisionmaking power. By fostering self-employment and providing credit access without collateral, microfinance serves as an effective tool for poverty alleviation and women’s empowerment. Women involved in microfinance institutions (MFIs) contribute to savings, income generation, and decision-making, with their influence often extending beyond the household level. The findings reveal that microfinance significantly enhances women’s economic and social empowerment through small-scale entrepreneurial projects, leading to improved income, decision-making authority, knowledge, and selfesteem. This positive correlation highlights microfinance as a catalyst for social transformation, poverty reduction, and sustainable development. The study underscores its pivotal role in promoting gender equality and uplifting marginalized communities, reinforcing the potential of microfinance in achieving inclusive growth.